Maslahah Mursalah Dalam Fatwa DSN-MUI Tentang Akad Wasathah (Keperantaraan) Dalam Bisnis Properti - Ahmad Saiful Hadi; Muhajir Muhajir; Fathudin Fathudin (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study explores the application of Maslahah Mursalah in the DSN-MUI fatwa concerning akad wasathah (intermediation) in business transactions. Maslahah Mursalah, as a principle in Islamic law, functions to regulate matters not explicitly covered by textual sources with the aim of achieving public benefit and preventing harm. This study's main emphasis is on the philosophical aspects of constructing the Maslahah Mursalah method in the DSN-MUI fatwa and its implications for business practices. The akad wasathah serves as an intermediary in business transactions, ensuring fair and beneficial agreements in accordance with Sharia principles. This study employs a descriptive qualitative approach to analyze the fatwa text and related literature, seeking to offer comprehensive insights about the application of Maslahah Mursalah within the framework of contemporary business law. The research findings are expected to offer significant contributions to the understanding of Sharia principles in business intermediation practices and provide recommendations for further development in fiqh muamalah.